2016
DOI: 10.4314/gmj.v49i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality in extrapulmonary tuberculosis patients at a teaching hospital in Ghana

Abstract: SUMMARYObjectives: To investigate the clinical manifestations and factors associated with mortality in patients with extrapulmonary tuberculosis (EPTB) at the Korle-Bu Teaching Hospital Chest Clinic in Accra, Ghana. Design: We conducted a retrospective chart review of patients treated for EPTB at the Chest Clinic between January 1, 2009 and December 31, 2011. Patients with a new diagnosis of EPTB without concomitant pulmonary disease, aged 18 years or older, and who were treated at the Chest Clinic were eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Disseminated TB is a severe form of EPTB usually associated with HIV infection with progression linked to the immuno-suppression and delayed treatment [29]. Given the HIV coinfection in our study population and with disseminated TB presenting with systemic symptoms, it is possible that delayed diagnosis may have contributed to this magnitude of disseminated TB [6,12, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disseminated TB is a severe form of EPTB usually associated with HIV infection with progression linked to the immuno-suppression and delayed treatment [29]. Given the HIV coinfection in our study population and with disseminated TB presenting with systemic symptoms, it is possible that delayed diagnosis may have contributed to this magnitude of disseminated TB [6,12, 20].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the peculiarities of EPTB including the atypical nature of presentation, understanding the epidemiology of EPTB in diverse settings is of interest given the relevance of EPTB to TB control [14]. Except for two teaching hospital setting studies on EPTB conducted in Ghana, studies on the EPTB in-country are limited [20,21]. The current study therefore sought to highlight the epidemiology of EPTB patients diagnosed from different categories of health facilities in Accra compared to pulmonary TB (PTB) patients and identify risk factors for mortality among EPTB patients.…”
Section: Introductionmentioning
confidence: 99%
“… 10 In Cameroon and Ghana, HIV co-infection with EPTB was 37.1% and 45.2%, respectively. 11 , 12 However, an estimate reported on the prevalence of EPTB among PLWHA was inconsistent and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As the immune system is suppressed, it leads to dissemination of TB to the other body organs which often carries a high risk of death and unfavorable prognosis [30]. Moreover, it might be due to drug mal-absorption among HIV patients 18] and delay in starting ART [31]. Additionally, previous studies conducted in different countries reported that mortality was high among patients who are not on ART [32][33][34] and those with low CD4 counts [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to delay in the diagnosis of EPTB or even missing the diagnosis completely [36]. Hence, EPTB patients will deteriorate more rapidly and have higher death rates as compared to pulmonary TB cases [31,37].…”
Section: Discussionmentioning
confidence: 99%